2017
DOI: 10.4236/ajcc.2017.64035
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of the Effects of Climate Variability on Agulu Lake, Anambra State, Nigeria

Abstract: The paper assessed the effect of variability of climatic elements on Agulu lake, Anambra State, Nigeria. Data for the work were acquired from Landsat website (landsat.org) for 35 years. Monthly records of the elements were collected from the synoptic meteorological station at Amawbia in Awka urban area. The penman model was used in the estimation of open water vapour from the lake. The analysis was performed using the output of the classified satellite imagery which was digitized for the entire year and the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The result shows an increase in evaporation for the months of March to May and October to November and a decrease in evaporation during the months of June, July, August and September from 1960 to 2016. The similarity observed between Evaporation and temperature models reiterate the result of the correlation between the two variables and re-emphasize the extent of influence of the temperature factor on evaporation on the pond (Nzoiwu et al, 2017). At the monthly scale, the analysis of the hydrological balance parameters makes it possible to distinguish two periods: a dry period and a wet period.…”
Section: Monthly Evolution Of Some Parameterssupporting
confidence: 53%
See 1 more Smart Citation
“…The result shows an increase in evaporation for the months of March to May and October to November and a decrease in evaporation during the months of June, July, August and September from 1960 to 2016. The similarity observed between Evaporation and temperature models reiterate the result of the correlation between the two variables and re-emphasize the extent of influence of the temperature factor on evaporation on the pond (Nzoiwu et al, 2017). At the monthly scale, the analysis of the hydrological balance parameters makes it possible to distinguish two periods: a dry period and a wet period.…”
Section: Monthly Evolution Of Some Parameterssupporting
confidence: 53%
“…This change in precipitation and temperature that accompanies climate change has the potential to alter the connectivity of ponds with biological implications (eg for migratory fish species), changes in volume, area, and pond depth, as well as other related limnological properties (Nzoiwu et al, 2017).…”
mentioning
confidence: 99%
“…These variations are mainly driven by climate change and human activities in their watershed. Ponds are strongly influenced by regional and global climate change in the short and long term (Nzoiwu et al, 2017). Their water level varies according to the precipitation / evaporation ratio, the groundwater inflow, the water abstraction rate and other factors.…”
mentioning
confidence: 99%
“…Thus, Ayoade (1975) also pointed out that an accurate assessment of the water resources of any region requires knowledge not only of the extent of rainfall and its spatial and temporal distribution, but also of the nature and magnitude loss of water by evaporation. This change in precipitation and temperature that accompanies climate change has the potential to alter the connectivity of ponds with biological implications (eg for migratory fish species), changes in volume, area, and pond depth, as well as other related limnological properties (Nzoiwu et al, 2017).…”
mentioning
confidence: 99%
“…A lot of studies on the effects of climate change had been done in various ecosystems such as climate variability in lakes [12] (Nzoiwu et al 2017), climate change impacts in crops and croplands in agro ecosystems [13] [14] as well as influence of climate change in land cover dynamics within the river basins which include mangrove, forest, beach, tidal areas, lagoon, river, settlements, barren salt areas and findings revealed that climate change is intensified by rapid urbanization in these ecosystems [14]. The current study did not in any way duplicate these earlier studies and would in fact use the results of recent studies including those cited above to validate the climate change risks and suitability of selected agri-aqua commodities as climate resilient livelihood options for selected communities in the country.…”
Section: Introductionmentioning
confidence: 99%